Platformizing Ubuntu? FinTech, Inclusion, and Mutual Help in Africa. Issue 4 (4th July 2022) - Rodima-Taylor, Daivi
ABSTRACT: The article explores the ways in which FinTech is constituted as a platform economy in two African countries, Kenya and South Africa. Investigating the intersection of FinTech with the social economies of African mutual help groups, it situates the evolvement of such groups in chronic instabilities shaped by the extractive legacies of colonialism and neoliberal restructuring. Seeking to contribute to wider debates about FinTech-mediated financial inclusion, the article contends that FinTech as a political economy does not simply formalize monetary and financial relations. Instead, it works explicitly at the intersection of formal and informal, by combining old and new, digital and non-digital, inanimate and peopled infrastructures. The paper studies how these sociotechnical assemblages are shaped by colonial legacies, transforming financial relations while carrying forward inequalities. It argues that the peculiar constellation of private capital and financial technology around digital platforms seeks to profit from these social networks that are often seen by FinTech actors as driven by various local versions of Ubuntu, the idea of human interdependence rooted in humanist African philosophy. The article makes novel contributions to several literatures, including those of rotating saving and credit associations, financial inclusion, and formalization.